2013 IEEE International Conference on Systems, Man, and Cybernetics 2013
DOI: 10.1109/smc.2013.450
|View full text |Cite
|
Sign up to set email alerts
|

Grasp Database That Covers Variation of Contact Region Usage

Abstract: This paper proposes a novel approach to build a human grasp database that considers contact regions for grasping posture synthesis. To cover all types of hand surface regions contacting an object when grasping, the grasp taxonomy from other research was extended. For each pattern of region usage, we collected several posture variations that differ in the distance between regions. In total, 801 postures were collected for 107 patterns of region usage. A posture to grasp a new object was generated by interpolati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…Since individual differences among ROMs are very large even in healthy [22] hands, only the rough features of the measured limited ROM in [21] were considered in the ROM limitation for the grasp synthesis in this paper. In the coordinate system of the hand model used by [10] and [11], it was confirmed that the ROM limitation by the taping method proposed in [21] restricted about 60% of the palmar abduction and 40% of the radial abduction.…”
Section: The Features Of Limited Rommentioning
confidence: 92%
See 4 more Smart Citations
“…Since individual differences among ROMs are very large even in healthy [22] hands, only the rough features of the measured limited ROM in [21] were considered in the ROM limitation for the grasp synthesis in this paper. In the coordinate system of the hand model used by [10] and [11], it was confirmed that the ROM limitation by the taping method proposed in [21] restricted about 60% of the palmar abduction and 40% of the radial abduction.…”
Section: The Features Of Limited Rommentioning
confidence: 92%
“…In this paper, the method of grasp synthesis for healthy hands proposed in [10] and [11] is applied to grasp synthesis for ROM-limited hands. This section explains an overview of the algorithm of grasp synthesis.…”
Section: Algorithm Of Grasp Synthesismentioning
confidence: 99%
See 3 more Smart Citations